The Effect of Nurses' Individual and Professional Characteristics and Career Decisions Regrets on Turnover Intention - Leyla Afşar Doğrusöz; Şehrinaz Polat; Tuğba Yeşilyurt; Nilgün Göktepe (Association of Nurse Managers, 2022)
Aim: The aim of this study is to examine the effects of nurses' individual and professional characteristics and regret about their career decision on their turnover intention. Method: This cross-sectional and descriptive study was conducted with 415 nurses working in a university hospital, where 1324 nurses were employed and volunteered to participate. The data were collected with a questionnaire consisting of three parts. The questionnaire consisted of the nurse introductory information form, the Career Decision Regret Scale, and the Turnover Intention Scale. Descriptive statistics, correlation and multiple regression (stepwise) analyses were used in the data analysis. Results: The mean score of the nurses' turnover intention scale was determined as 2.33 +- 1.10 and the total mean score of the career regret scale was 71.08 +- 24.43. In the regression analysis, the conclusion was that the turnover intention was affected by marital status and career decision regret (R2=19.5%; p<,001). Conclusion: The results of the study show that nurses' turnover intention is influenced by marital status and regret about the career decision. Policymakers should establish national strategies for organizing early intervention programs, such as informing students about career choices and career counseling services before choosing a university/occupation. Additionally, it is recommended by the institution managers to adopt organizational strategies to support nurse welfare, empathy, and professional development, and to improve the working environment, despite the possibility of nurses leaving the job due to professional decision regrets.